2004
DOI: 10.1021/jo035507h
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Proposed Structures of Indole Alkaloids Lyaline and Lyadine

Abstract: The harman-1,4-dihydropyridines 1 and 2, which constitute the originally proposed structures for the indole alkaloids lyaline and lyadine, have been synthesized, and their NMR data have been compared with those available for the natural products. Due to the discrepancies in the spectral data, the structures of lyadine and lyaline should be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The 1 H-NMR and 13 C-NMR of Compound 14 are consistent with those reported in the previous study, so it was concluded that Compound 14 is 5-(1′-hydroxyethyl) nicotinic acid methyl ester [ 27 ].…”
Section: Methodssupporting
confidence: 83%
“…The 1 H-NMR and 13 C-NMR of Compound 14 are consistent with those reported in the previous study, so it was concluded that Compound 14 is 5-(1′-hydroxyethyl) nicotinic acid methyl ester [ 27 ].…”
Section: Methodssupporting
confidence: 83%
“…The trivial names of the same molecules are given in Figure B. As with any analysis of this type, it does assume that the structures are correct, and, for instance, at least that for lyaline (left‐hand‐most structure, marked green) is in doubt . However, we do not rehearse these in further detail, save to mention that the largest cluster contains a great many sterols, molecules that were among the most abundant both in terms of approved drugs and of endogenous metabolites …”
Section: Resultsmentioning
confidence: 98%
“…Later Gatta and co-workers [34] reported an improved synthesis of methyl 1-formyl-9-H-pyrido [3,4-b] indole-3-carboxylate from 1-methyl-3methoxycarbonyl-β-carboline via oxidation with SeO 2 in dioxane. These workers further reported the application of 1-formyl-9H-β-carboline for the synthesis of canthin-6-one [35].…”
Section: Synthesis Of β-Carbolinementioning
confidence: 99%